Electrospun Nd3+‐Doped LiMn2O4 Nanofibers as High‐Performance Cathode Material for Li‐Ion Capacitors. Issue 8 (29th May 2017) - Vijayan, Shobana; Kirubasankar, Balakrishnan; Pazhamalai, Parthiban; Solarajan, Arun Kumar; Angaiah, Subramania
Abstract: Electrospun high‐voltage spinel‐typeLiNd0.01 Mn1.99 O4 nanofibers (LNdMO NFs) were successfully prepared through the electrospinning technique. The thermal behavior of the electrospun precursor fibrous mat was assessed by thermogravimetric/differential thermal analysis. The crystallite structure and phase purity of Nd 3+ ‐doped LiMn2 O4 was confirmed by X‐ray diffraction studies. The chemical structure of the electrospun LNdMO NFs was characterized by Raman spectroscopy studies. The morphology of the nanofibers was examined by using field‐emission scanning electron microscopy. A Li‐ion capacitor (LIC) coin cell was fabricated by using high‐voltage insertion LNdMO NFs as the cathode and black pearl carbon as the anode with electrospun PVdF membrane containing 1 M LiNO3 as the separator and electrolyte. The electrochemical performance of the assembled LIC coin cell was characterized by using cyclic voltammetry, galvanostatic charge−discharge and electrochemical impedance spectroscopy. The LIC was capable of operating over wide potential window of 1.6 V with excellent capacitance retention of 86 % even after 2500 continuous galvanostatic charge−discharge cycles at a constant current density of 1 A g −1 . Furthermore, LIC delivered an energy density of 17 Wh kg −1 and a power density of 397 W kg −1 . Moreover, these results show that Nd 3+ ‐doped LiMn2 O4 NFs can be considered a promising electroactive cathode material for LICs. Abstract : Li‐ion capacitor Caps. off : A simple electrospinning technique is used to develop high‐voltage spinel‐type LiNd0.01 Mn0.99 O4 nanofibers (LNdMO NFs) with a high specific capacitance of 395 F g −1, which can be used as a positive electrode material for a Li‐ion capacitor (LIC). Operating in a potential window of 1.6 V, this LIC delivers an energy density of 17 Wh kg −1 and a power density of 397 W kg −1 .